2008
DOI: 10.1038/nsmb.1394
|View full text |Cite
|
Sign up to set email alerts
|

GroEL stimulates protein folding through forced unfolding

Abstract: Many proteins cannot fold without the assistance of chaperonin machines like GroEL and GroES. The nature of this assistance, however, remains poorly understood. Here we demonstrate that unfolding of a substrate protein by GroEL enhances protein folding. We first show that capture of a protein on the open ring of a GroEL-ADP-GroES complex, GroEL's physiological acceptor state for non-native proteins in vivo, leaves the substrate protein in an unexpectedly compact state. Subsequent binding of ATP to the same Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
209
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(221 citation statements)
references
References 60 publications
8
209
2
2
Order By: Relevance
“…Mixing the SR1-rhodanese complexes with 2 mM ATP and 2 μM GroES results in complete binding of GroES to SR1 in ∼200 ms (48), which triggers the release of the substrate protein into the chaperonin cavity. Active unfolding of the substrate protein driven by the conformational changes of the apical domains of GroEL upon binding of ATP and GroES has been proposed to support protein folding (28,49,50). Surprisingly, we observed no obvious changes in the transfer efficiency histograms on a timescale from milliseconds to seconds (Fig.…”
Section: Resultsmentioning
confidence: 39%
“…Mixing the SR1-rhodanese complexes with 2 mM ATP and 2 μM GroES results in complete binding of GroES to SR1 in ∼200 ms (48), which triggers the release of the substrate protein into the chaperonin cavity. Active unfolding of the substrate protein driven by the conformational changes of the apical domains of GroEL upon binding of ATP and GroES has been proposed to support protein folding (28,49,50). Surprisingly, we observed no obvious changes in the transfer efficiency histograms on a timescale from milliseconds to seconds (Fig.…”
Section: Resultsmentioning
confidence: 39%
“…A number of studies have made it clear that the polypeptide binding step can rescue misfolded substrate proteins from kinetically trapped states that occur during folding (e.g., 4, 5), despite the lack of stable secondary structure in such conformations (6, 7). Such rescue has been associated with topological ''stretching'' of the substrate protein, as observed in a number of FRET studies (5,8,9). Substrate protein is released during large ATP/GroES-directed rigid body movements of the GroEL apical domains into the GroES-domed hydrophilic chamber, in which it proceeds to fold (10-12).…”
mentioning
confidence: 99%
“…Does polypeptide arrive first? This has been assumed in a number of studies in vitro, where an order of addition has been programmed in which substrate is first incubated with such asymmetrical complexes, followed by addition of ATP (8,9). In such studies, there have been observations that ATP addition produced additional stretching of nonnative protein, and it was suggested that this could constitute a necessary ATP-mediated ''forced unfolding'' step.…”
mentioning
confidence: 99%
“…In particular, small ATP-directed elevation and twisting movements serve to recruit the cochaperonin lid structure, GroES (6). This triggers further large movements of the apical domains, Ϸ60°elevation and Ϸ120°clockwise twist, that release the substrate protein off the dislocating hydrophobic surface, effectively ejecting the substrate into a hydrophilic GroESencapsulated chamber where productive folding ensues (4,5,(7)(8)(9)(10)(11)(12)(13)(14). This step of ATP-mediated activation requires less than 1 s (9,12).…”
mentioning
confidence: 99%